2011
DOI: 10.1111/j.1752-0606.2011.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Methods Research in Marriage and Family Therapy: A Content Analysis

Abstract: Considering mixed methods research is gaining reputability in the marriage and family therapy field (Research methods in family therapy, Guilford, 2005), we conducted a mixed methods content analysis to examine the prevalence and quality of published mixed and multimethod research during the past 10 years in eight prominent MFT journals (N = 32). Our purpose was to determine the characteristics of studies that utilized both qualitative and quantitative methods, the themes of the rationales for combining method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 48 publications
0
28
0
Order By: Relevance
“…According to Sells et al (1999), the multimethod model (combination of a variety of methodologies) is the most comprehensive for family therapy research, since it benefits from the potential of both methods and promotes the connection between theory, research and clinical practice. Specifically, the mixed methods research model (quantitative and qualitative research) seems to have much to offer to the SFT field since it allows therapists to understand both process of change and interventions evaluation (Gambrel & Butler, 2013). However, the systemic researchers are still very conditioned by the traditional courses of investigation and have therefore been resisting the adoption of the mixed method or multimethod model.…”
Section: Methodological Questions Inherent To the Study Of Family Thementioning
confidence: 99%
See 2 more Smart Citations
“…According to Sells et al (1999), the multimethod model (combination of a variety of methodologies) is the most comprehensive for family therapy research, since it benefits from the potential of both methods and promotes the connection between theory, research and clinical practice. Specifically, the mixed methods research model (quantitative and qualitative research) seems to have much to offer to the SFT field since it allows therapists to understand both process of change and interventions evaluation (Gambrel & Butler, 2013). However, the systemic researchers are still very conditioned by the traditional courses of investigation and have therefore been resisting the adoption of the mixed method or multimethod model.…”
Section: Methodological Questions Inherent To the Study Of Family Thementioning
confidence: 99%
“…However, the systemic researchers are still very conditioned by the traditional courses of investigation and have therefore been resisting the adoption of the mixed method or multimethod model. Although the benefits of the mixed methods model are evident to researchers, little is known about its use in family therapy investigation studies, which results in a lack of mixed methods studies in SFT overall (Gambrel & Butler, 2013). In this study, we identified and selected only one mixed method study (Blow et al, 2009).…”
Section: Methodological Questions Inherent To the Study Of Family Thementioning
confidence: 99%
See 1 more Smart Citation
“…Within engineering education specifically, studies that incorporate mixing often lack diversity in design (Kajfez & Creamer, ), with interviews and surveys as the conventional qualitative and quantitative data sources (see Crede & Borrego, ); the homogenous designs also typify other fields in the social sciences (e.g., Bryman, ; Gambrel & Vi, ). Bryman () argues for a broader exploration of possibilities within mixed methods, particularly with mixing strategies for analysis, which are rarely used in practice even when the data afford the opportunity (O'Cathain et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This researcher had no background information about, for example, the children's age or gender. The children's interview answers were studied using content analysis (Gambrel and Butler, 2013).…”
Section: Methodsmentioning
confidence: 99%